Staphylococcus aureus as an intracellular pathogen: the role of small colony variants - Sendi, Parham; Proctor, Richard A. (Trends in microbiology (Regular ed.), 2009)
Increasing evidence indicates that Staphylococcus aureus might be a facultative intracellular pathogen. In particular, certain subpopulations, called small colony variants (SCVs), seem to be well adapted to the intracellular milieu. When compared to ‘normal’ staphylococcal strains, SCVs show increased uptake by host cells, resistance to intracellular defenses and reduced stimulation of host defenses. We propose that the ability to form two subpopulations with different phenotypes might allow S. aureus the option for both extra- cellular and intra-cellular survival in the host.